Penerapan Profil Pelajaran Pancasila Melalui Kegiatan Pasraman Kilat Pada Siswa Siswi di SMA Negeri 1 Tembuku - Budiartawan, I Mangku (Samsara Institute Publisher, 2025)
Pancasila Student Profile is a characteristic of the character and competencies that students are expected to achieve, which is based on the noble values of Pancasila. As in the circular letter from the governor of Bali regarding the implementation of flash pasraman in educational units, especially high schools/vocational schools in the province of Bali, to carry out flash pasraman activities as a forum for preserving cultural values and cultural traditions of the Hindu religion. The problem formulation is what is the role of Pasraman Kilat in strengthening the Pancasila Student Profile at SMA Negeri 1 Tembuku. Then the purpose of writing is to provide students with an understanding of strengthening the Pancasila Student Profile. The discussion is that the Pancasila student profile is a mandate of the Merdeka Curriculum which has elements namely: a) Faith, devotion to God Almighty, and noble character, b) global diversity, c) independence, d) critical thinking, e) working together and f) Creative. Furthermore, the Pasraman Kilat activity is a culture or tradition of the noble cultural heritage of the Hindu religion which must be maintained and implemented as part of preserving it.